The immune factors have complex causal regulation effects on inflammatory bowel disease - Qiu, Binxu; Zhang, Tao; Qin, Xinxin; Ma, Shengjie; Wang, Quan (Frontiers in Immunology, 2024)
Although a correlation between immune cell phenotypes and inflammatory bowel disease (IBD) has been established, a causal relationship remains unestablished.To assess causal associations between immune cell phenotypes and IBD and its subtypes, we employed Mendelian randomization (MR) methods and genome-wide association studies (GWAS) summary statistics. The primary outcomes were determined based on the inverse variance weighting (IVW) results, with the assessment of heterogeneity and pleiotropy conducted through Cochrane's Q-test and MR-Egger. The stability of the MR results was then examined using leave-one-out analysis, and false discovery rate (FDR) correction was applied to evaluate the strength of the causal relationship between exposure and outcome. Furthermore, to identify immunophenotypes strongly associated with IBD, a meta-integration of the effect values of all positive results in both datasets was conducted.The analysis of 731 immune cell phenotypes and IBD using MR techniques revealed potential causal associations between 26 phenotypes and IBD. Subsequent metaintegration of the two datasets provided evidence of solid causal associations between 20 immune phenotypes and IBD and its subtypes. Nominal causal associations were also identified in the remaining six immune phenotypes and IBD and its subtypes.Our study confirms causal solid associations between 20 immune phenotypes and IBD, thus guiding future clinical studies.